Media Games Edukatif sebagai Upaya Meningkatkan Minat Belajar pada Pembelajaran Pendidikan Agama Kristen - Arestu Yulanda; Irma Nelyani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the role of educational game-based learning media and analyze its contribution to increasing students’ interest in learning Christian Religious Education (CRE). The research employed a qualitative descriptive method using a library research approach, drawing data from various relevant sources, including books, scientific journals, and scholarly articles related to educational games, learning interest, and Christian Religious Education. The findings indicate that educational game-based learning media can create a more engaging, interactive, and enjoyable learning environment, thereby encouraging students’ active participation in the learning process. The use of educational games also enhances students’ motivation, concentration, and enthusiasm in learning Christian Religious Education materials. Furthermore, this learning media helps students understand Christian values more contextually through meaningful learning experiences. The successful implementation of educational game-based learning media is influenced by teachers’ creativity in designing and selecting games that align with learning objectives and students’ characteristics. Therefore, educational game-based learning media can serve as an effective alternative for increasing students’ learning interest while supporting the achievement of Christian Religious Education learning objectives.